Formation of N-sulfonyl imines from iminoiodinanes by iodine-promoted, N-centered radical sulfonamidation of aldehydes. Issue 43 (27th October 2017) - Hopkins, Megan D.; Scott, Kristina A.; DeMier, Brettany C.; Morgan, Heather R.; Macgruder, Jesse A.; Lamar, Angus A.
Abstract : A light-promoted, non-traditional carbonyl activation via a N-centered radical (NCR) species to produce activated imines using iminoiodinanes is reported. Abstract : A mild and operationally convenient formation of synthetically valuable N -sulfonyl imines from a range of aryl aldehydes by reaction with iminoiodinanes (PhINZ) and I2 has been developed. According to mechanistic experiments described within, the reaction is speculated to proceed through an unconventional light-promoted, N-centered radical (NCR) pathway involving a N, N -diiodosulfonamide reactive species. This method not only provides a new pathway toward the production of activated imines, but also serves as an example of a non-traditional means of carbonyl activation via an NCR species.